Odpowiedź :
a) 2x+1=9
2x=9-1
2x=8 /:2
x=4
b)5y+5=5
5y=5-5
5y=0 /:5
y=0
c)2z-7=9
2z=9+7
2z=16 /:2
z=8
d)0=3+11d
-11d=3 /:(-11)
d=-3/11
e)3x-15=1
3x=1+15
3x=16 /:3
x=3/16
f)4y-24=3y
4y-3y=24
y=24
g)4x-3=3x+5
4x-3x=5+3
x=8
h)5x+2=7-3x
5x+3x=7-2
8x=5 /:8
x=1 3/4
i)3(x-1)=0
3x-3=0
3x=3 /:3
x=1
j-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30 /:(-6)
x=-5
2x=9-1
2x=8 /:2
x=4
b)5y+5=5
5y=5-5
5y=0 /:5
y=0
c)2z-7=9
2z=9+7
2z=16 /:2
z=8
d)0=3+11d
-11d=3 /:(-11)
d=-3/11
e)3x-15=1
3x=1+15
3x=16 /:3
x=3/16
f)4y-24=3y
4y-3y=24
y=24
g)4x-3=3x+5
4x-3x=5+3
x=8
h)5x+2=7-3x
5x+3x=7-2
8x=5 /:8
x=1 3/4
i)3(x-1)=0
3x-3=0
3x=3 /:3
x=1
j-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30 /:(-6)
x=-5
a) 2x+1=9
2x=9-1
2x=8 / :2
x=4
b) 5y+5=5
5y=5-5
5y=0
y=0
c) 2z-7=9
2z=9+7
2z=16 / :2
z=8
d) 0=3+11d
-3=11d /:11
-3/11 = d
e) 3x-15=1
3x=1+15
3x=16 / :3
x=16/3
f)4y-24=3y
4y-3y=24
y=24
g)4x-3=3x+5
4x-3x=5+3
x=8
h)5x+2=7-3x
5x+3x=7-2
8x=5 / :8
x=5/8
i)3(x-1)=0
3x-3=0
3x=3 / :3
x=1
j-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30 / :(-6)
x= -5
2x=9-1
2x=8 / :2
x=4
b) 5y+5=5
5y=5-5
5y=0
y=0
c) 2z-7=9
2z=9+7
2z=16 / :2
z=8
d) 0=3+11d
-3=11d /:11
-3/11 = d
e) 3x-15=1
3x=1+15
3x=16 / :3
x=16/3
f)4y-24=3y
4y-3y=24
y=24
g)4x-3=3x+5
4x-3x=5+3
x=8
h)5x+2=7-3x
5x+3x=7-2
8x=5 / :8
x=5/8
i)3(x-1)=0
3x-3=0
3x=3 / :3
x=1
j-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30 / :(-6)
x= -5
a)2x+1=9 I -1
2x=8 I:2
x=4
b)
5y+5=5 I-5
5y=0 I:5
y=0
c)2z-7=9 I+7
2z=16 I:2
z=8
d)0=3+11d I-3
-3=11d I:11
d= -3/11 / - oznacza kreskę ułamkową
e)3x-15=1 I+15
3x= 16 I:3
x= 16/3= 5całych 1/3
f)4y-24=3y I-3y
y-24=0 I+24
y=24
g)4x-3=3x+5 I+3
4x=3x+8 I-3x
x=8
h)5x+2=7-3x I+3x
8x+2=7 I -2
8x=5 I:8
x= 5/8
i)3(x-1)=0
3x-3=0 I +3
3x=3
x=1
j-6(x+1)=24
6x +6= 24 I -6
6x= 18 I:6
x=3
2x=8 I:2
x=4
b)
5y+5=5 I-5
5y=0 I:5
y=0
c)2z-7=9 I+7
2z=16 I:2
z=8
d)0=3+11d I-3
-3=11d I:11
d= -3/11 / - oznacza kreskę ułamkową
e)3x-15=1 I+15
3x= 16 I:3
x= 16/3= 5całych 1/3
f)4y-24=3y I-3y
y-24=0 I+24
y=24
g)4x-3=3x+5 I+3
4x=3x+8 I-3x
x=8
h)5x+2=7-3x I+3x
8x+2=7 I -2
8x=5 I:8
x= 5/8
i)3(x-1)=0
3x-3=0 I +3
3x=3
x=1
j-6(x+1)=24
6x +6= 24 I -6
6x= 18 I:6
x=3